Immunoscintigraphy and Radioimmunotherapy in Patients with Pancreatic Carcinoma - Montz, R.; Klapdor, R.; Rothe, B.; Heller, M. (Nuklearmedizin - NuclearMedicine, 1986)
A new monoclonal antibody (BW 494/32) labeled with 131I or 111ln was used for planar and tomographic immunoscintigraphy (IS) in patients with pancreatic carcinoma. It appears that a) IS for pancreatic carcinoma and its metastases remains a hopeful but still difficult procedure and b) labeling with 111In is of advantage and results in more convincing images in the case of tumor lesions distant from liver and spleen. Attempts at radioimmunotherapy with 131l-anti- CA19-9 and with 131l-494/32 in a patient with local recurrence of a pancreatic cancer and with large liver metastases were without success because of extremely poor blood supply to the metastatic tumor masses. Intraarterial infusion of the tracer without or with blockade and perfusion of the common hepatic artery with saline solution could not enhance the tracer uptake compared to that after intravenous infusion. High intratumoral concentrations, however, as achieved e. g. by intratumoral instillation in animal studies, represent a necessary precondition for effective β-irradiation of tumor lesions.Ein neuer Antikörper, BW 494/32, markiert mit 131J oder mit 111In, wurde für die planare und tomographische Immunszintigraphie (IS) bei Patienten mit Pankreaskarzinom eingesetzt. Die Ergebnisse lassen sich derart zusammenfassen, daß a) die Immunszintigraphie zur Darstellung des Pankreaskarzioms und seiner Metastasen nach wie vor ein zukunftsträchtiges, aber schwieriges Verfahren bleibt, und b) die 111In-Markierung die Befunde außerhalb von Leber und Milz diagnostisch verbessert. Versuche einer Radioimmuntherapie mit 131J-anti-CA 19-9 und mit 131J-494/32 bei einem Patienten mit Lokalrezidiv und ausgedehnter Lebermetastasierung blieben erfolglos wegen sehr geringer Vaskularisation dieser Tumore. Auch die intraarterielle Infusion, sogar mit Blockade und vorheriger Perfusion der A. hepatica communis mit Kochsalzlösung, ergab keine höhere Anreicherung des Tracers als nach intravenöser Infusion. Eine primär hohe Konzentration der 131J-markierten Antikörper, wie sie in Tierversuchen durch intratumorale Instillation erreicht werden kann, wäre aber die Voraussetzung für eine wirksame Radioimmunotherapie mit β-Strahlern.